TOWARDS REUSE OF AQUACULTURE EFFLUENTS FOR SUSTAINABLE CROP PRODUCTION IN THE DRYLANDS: A PRELIMINARY INVESTIGATION (FUDMA JOURNAL OF SCIENCES, 2024)
The aquaculture industry generates substantial amounts of effluents that may cause environmental pollution if not properly handled. However, since it may contain nutrients, aquaculture effluents could offer a sustainable source of irrigation water in the drylands, which are characterized by water scarcity. This paper provides preliminary findings on aquaculture effluent generation and management in Kano State which is located in Nigerian drylands. Surveys were conducted to obtain information related to the production size, sources of water, and effluent handling. 87% of the surveyed farms are small-scale and medium-scale enterprises, with capacities below 5000 fish. Catfish and Tilapia are the commonly produced fish, with 67% of the farms producing the former. Groundwater is the common source of water utilized by farms, accounting for about 72% of the total. Our findings indicate that there are no established criteria for changing the pond water, with the farms considering either the color of the water or its duration in the pond. Most of the farms change the water every 1 to 2 weeks while considering the change in color as the major criterion. The majority of the farms discharge the effluents directly without any treatment. Although some of the farms claimed to be treating their effluents, we could not establish the presence of treatment technologies on the farms. Unfortunately, most of the farmers are unaware of the environmental implications of discharging the effluents without treatment. Further studies are needed to characterize these effluents and to evaluate their suitability as irrigation water.
Keywords: Sustainability; Water management; Peri-urban agriculture; Circular economy; Irrigation